Discovering underground bat hibernacula in lowland eastern Europe - Godlevska, Lena; Shpak, Aliaksei; Savchenko, Mariia; Vorobei, Pavlo (Zenodo, 2023)
(Uploaded by Plazi for the Bat Literature Project) The importance of underground hibernacula for the conservation of bats and monitoring their populations is well-recognized. However, the lowland territory of Belarus, with absent natural caves and suitable for bats mines, was one of the least surveyed European regions in terms of underground bat sites, and especially hibernacula. To address this knowledge gap, in 2020, we conducted a broadscale one winter bat survey, exploring 90 underground sites (basements, cellars, church crypts, fortifications, and facilities of abandoned Soviet missile bases) in various parts of Belarus. To our knowledge, none of these sites had been examined for bats before. In 56 of the 90 underground sites, we discovered hibernating bats (a total of 1054 ind.) of six species: Barbastella barbastellus (78.5% of all bats), Myotis daubentonii (7.4%), Plecotus auritus (5.1%), Eptesicus nilssonii (4.9%), Myotis brandtii and Eptesicus serotinus (in sum, 2%). The distribution of bats among the hibernacula was highly uneven (with NMe = 3; Nav = 19 ind.). In 76% of the hibernacula, the number of bats was between 1 and 10 individuals per site, which accounted for approximately 10% of all bats recorded during the survey. Only in five sites we found over 50 bats. One to four species were present in each site, with one species found in 58% of the hibernacula. We suppose that the small number of species and relatively small number of bats per hibernaculum is characteristic of the study region. This supports the idea that selecting key underground bat sites for their conservation and monitoring should be done regionally and only after obtaining primary data about bat species and their numbers in a sufficient number of sites. Our data significantly expands knowledge about underground bat hibernacula in the large lowland territory of eastern Europe and may serve as a starting point for further monitoring.